2011
DOI: 10.2519/jospt.2011.3545
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Clinical Factors Related to Stage I Posterior Tibial Tendon Dysfunction

Abstract: Posterior tibial tendon dysfunction (PTTD) is a progressive and debilitating condition that is estimated to affect nearly 5 million people in the United States. 7 In the early stages (stage I) of the condition, PTTD is a common running-related injury. 31While the aetiology of PTTD has not been established, it is considered multifactorial in nature and has generally been related to progressive alterations in arch structure, muscular strength, and gait biomechanics. T T BACKGROUND:PTTD is a progressive conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
0
45
2
3
Order By: Relevance
“…Combined isometric forefoot adduction and subtalar inversion strength in plantar flexion was reported in three studies [22, 24, 28]. Pooled data from two studies that measured strength in 90 degrees of knee flexion [22, 24] revealed a moderate deficit (based on an SMD value of − 1.19) in PTTD compared to controls (MD − 0.27 N/kg) (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Combined isometric forefoot adduction and subtalar inversion strength in plantar flexion was reported in three studies [22, 24, 28]. Pooled data from two studies that measured strength in 90 degrees of knee flexion [22, 24] revealed a moderate deficit (based on an SMD value of − 1.19) in PTTD compared to controls (MD − 0.27 N/kg) (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…2). The other study measured forefoot abduction and subtalar inversion strength in full knee extension [28] and showed no difference (MD 0.01 N/kg). It was excluded from the pooled analysis due to heterogeneity of testing position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La causa del fracaso quirúrgico, incluso con una extirpación en su totalidad, vendría dada por no reparar la causa etiológica, es decir, por no reparar la herniación de la vaina tendinosa, causante de la extravasación de mucina, origen del ganglión y la alteración funcional que la produjo. En este sentido, estudios anatomopatológicos demuestran que la disfunción del tendón del músculo tibial posterior, como el caso presentado, puede producir tendinitis 15,16 , tendinosis y fibrosis con o sin rotura de dicho tendón 17 . Con mucha frecuencia la causa patomecánica de la hernia tendinosa (y consiguientemente del quiste sinovial) está muy alejada del lugar donde se produce esta lesión paratumoral por lo que un adecuado tratamiento ortopodológico y/o rehabilitador son determinantes para evitar recidivas postquirúrgicas.…”
Section: Discussionunclassified
“…Athletes with a clear pes planovalgus or with a forefoot abduction are prone to place greater strain on the muscle (Rabbito et al 2011 ). Posteromedial palpation will reveal tenderness, discrete swelling and occasionally crepitus.…”
Section: Tibialis Posterior Tendonmentioning
confidence: 99%